Quantile Regression Analysis for Students’ Difficulty Level in Learning Statistics Online - Leomarich F Casinillo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Statistics learning in the time of distance education makes students uneasy due to the difficulties in the learning environment and processes. This article aims to analyze the level of difficulty faced by students in statistics distance education and captures the causal factors affecting it. Cross-sectional secondary data were used from a current study in literature and described by standard statistical measures. The study utilized the level of difficulty in learning statistics during online setup as the dependent variable in the form of a scale of 1 to 10. The study used standard descriptive measures. Moreover, this study also use quantile regression models were constructed. Results depicted that students were facing